Conscious thought does not guide moment-to-moment actions—it serves social and cultural functions - Masicampo, E. J.; Baumeister, Roy F. (Frontiers in Psychology, 2013)
Humans enjoy a private, mental life that is richer and more vivid than that of any other animal. Yet as central as the conscious experience is to human life, numerous disciplines have long struggled to explain it. The present paper reviews the latest theories and evidence from psychology that addresses what conscious thought is and how it affects human behavior. We suggest that conscious thought adapts human behavior to life in complex society and culture. First, we review research challenging the common notion that conscious thought directly guides and controls action. Second, we present an alternative view—that conscious thought processes actions and events that are typically removed from the here and now, and that it indirectly shapes action to favor culturally adaptive responses. Third, we summarize recent empirical work on conscious thought, which generally supports this alternative view. We see conscious thought as the place where the unconscious mind assembles ideas so as to reach new conclusions about how best to behave, or what outcomes to pursue or avoid. Rather than directly controlling action, conscious thought provides the input from these kinds of mental simulations to the executive. Conscious thought offers insights about the past and future, socially shared information, and cultural rules. Without it, the complex forms of social and cultural coordination that define human life would not be possible.